Attitude stabilization and test validation of underactuated post-capture combination with multiple disturbances. (June 2019) - Chen, Shiyu; Sun, Chong; Guo, Linli; Zhu, Zhanxia; Wang, Zheng; Yuan, Jianping
This paper aims to address attitude stabilization control of an underactuated post-capture combination and achieve test validation based on the magnetism–buoyancy hybrid micro-gravity experiment system (MBHMES). Using a precise reduced model, a cascade control law is proposed to solve the issue theoretically. First, an advanced quaternion-based kinematic control law is proposed to stabilize the attitude of the non-symmetric post-capture combination. This control law can overcome the singularity brought about by the small initial attitude under the consideration of uncontrolled angular velocity. Then, considering the existence of multiple disturbances introduced by the fluid flow and electromagnetic force, an effective adaptive dynamic controller is proposed to meet the attitude requirement and reduce the negative effect of the multiple disturbances. For test demonstrations, a scenario of a base body capturing the target with robotics, to achieve attitude stabilization expectation, is described. Simulation results demonstrate the performance of the cascade control laws and test data show the effectiveness of the proposed method.